Metabolomics reveals diet-derived plant polyphenols accumulate in physiological bone - McCullagh, J; Trentacoste, A; Deviese, T; Grazia Cappai, M; Tripp, J; Ditchfield, P; Hedges, R; Alldritt, I (Springer Nature, 2019)
Plant-derived secondary metabolites consumed in the diet, especially polyphenolic compounds, are known to have a range of positive health effects. They are present in circulation after ingestion and absorption and can be sequestered into cells within particular organs, but have rarely been investigated systematically in osteological tissues. However, a small number of polyphenols and similar molecules are known to bind to bone. For example alizarin, a plant derived anthraquinone and tetracycline (a naturally occurring antibiotic), are both absorbed into bone from circulation during bone formation and are used to monitor mineralization in osteological studies. Both molecules have also been identified serendipitously in archaeological human bones derived from natural sources in the diet. Whether an analogous mechanism of sequestration extends to additional diet-derived plant-polyphenols has not previously been systematically studied. We investigated whether a range of diet-derived polyphenol-like compounds bind to bone using untargeted metabolomics applied to the analysis of bone extracts from pigs fed an acorn-based diet. We analysed the diet which was rich in ellagitannins, extracts from the pig bones and surrounding tissue, post-mortem. We found direct evidence of multiple polyphenolic compounds in these extracts and matched them to the diet. We also showed that these compounds were present in the bone but not surrounding tissues. We also provide data showing that a range of polyphenolic compounds bind to hydroxyapatite in vitro. The evidence for polyphenol sequestration into physiological bone, and the range and specificity of polyphenols in human and animal diets, raises intriguing questions about potential effects on bone formation and bone health. Further studies are needed to determine the stability of the sequestered molecules post-mortem but there is also potential for (palaeo)dietary reconstruction and forensic applications.